Effects of phrenic nerve magnetic stimulation on respiratory function in stroke patients: study protocol for a randomised controlled trial - Jun Ni; Zhiyong Wang; Xiaoli Xu; Qiong Han; Zhipeng Yan (BMJ Open)
Introduction Respiratory dysfunction is a notable complication in stroke patients, in which the diaphragm, as the primary respiratory muscle, directly influences lung function. Repetitive peripheral magnetic stimulation (rPMS) is a new, non-invasive approach that is used to treat brain and nerve problems. Few studies have examined the effect of magnetic stimulation on the phrenic nerve, breathing and diaphragm in stroke patients. This study aims to assess the effect of magnetic phrenic nerve stimulation on respiratory muscle function and lung function in adults with stroke. The results of this study may provide a promising approach to managing respiratory dysfunction in stroke patients.Methods and analysis This randomised controlled trial is designed to compare the effectiveness of bilateral magnetic phrenic nerve stimulation (rPMS) and conventional rehabilitation training in enhancing respiratory muscle strength, lung function indicators, diaphragmatic excursion and diaphragm thickness in patients with respiratory muscle weakness. Thirty patients admitted to the First Hospital of Fujian Medical University will be included in this study. Participants in the intervention group will undergo daily bilateral magnetic phrenic nerve stimulation for 2 weeks. Stimulation will be administered at a frequency of 25 Hz, with a pulse duration of 1.1 s and an inter-pulse interval of 5.9 s, for 5 days each week. Primary outcome measures will be assessed at baseline and after 2 weeks (end of the intervention) to evaluate the efficacy of rPMS compared with conventional rehabilitation techniques.Ethics and dissemination Before commencing the study, all participants will receive a comprehensive explanation of the study procedures, including the assessments. They will also be provided informed consent forms for review, completion and signing. This study was approved by the Ethics Committee for Research at the First Affiliated Hospital of Fujian Medical University (No.: MRCTA, ECFAH of FMU [2021]641, dated 10 November 2023) (Appendix Ⅰ & Ⅱ). The trial protocol will strictly adhere to the Uniform Standards for Reporting of Trials (CONSORT) statement. The trial has been registered with the Chinese Clinical Trial Registry.Dissemination of individual findings for each participant will be available at the end of the study. The findings will be disseminated to different interest groups, participants or other patients with respiratory dysfunction through journal papers and/or conference presentations. The results of the primary trial will be submitted for publication in a peer-reviewed journal.Registration ChiCTR2300075669, registered on 12 September 2023.